Strategi Kepala Madrasah dalam Meningkatkan Kualitas Pendidikan: Studi Kasus pada MI Muhammadiyah Dukuh, Watulimo, Trenggalek - Falah, Anta Khoirul Miftahul; Fuadiy, Moch. Rizal (DIMAR: Jurnal Pendidikan Islam, 2023)
This article discusses a research aimed at understanding the strategy of the Head of Madrasah Ibtidaiyah Muhammadiyah Dukuh in the Watulimo Subdistrict, Tenggalek Regency, with the goal of improving the quality of education. Despite facing limitations in the number of students (40 students) and personnel (10 teachers), the madrasah has successfully maintained its level of quality and continues to receive positive interest from the community. The research also aims to identify challenges that arise during the implementation of the strategy and formulate solution-oriented steps to overcome these obstacles, with the objective of ensuring that the applied strategy achieves optimal results. The research methodology employed is a descriptive-qualitative approach, using observation, interviews, and documentation methods for data collection. The findings indicate that the strategy implemented by the madrasah head involves a series of stages, starting from communication management and analysis of the internal and external environment of the madrasah, formulation of strategies based on coordination with internal elements of the madrasah and input from the community, to the implementation and evaluation of the strategy. Identified obstacles involve inhibiting factors such as limited facilities and infrastructure, as well as a shortage of experts proficient in flagship programs. The solution-oriented efforts include optimizing the use of existing facilities and infrastructure, enhancing the quality of educators through teacher professional development training, and involving active participation from the community in flagship activities. With these steps, it is hoped that the applied strategy can be executed optimally, overcome emerging challenges, and produce optimal educational quality. As an added value, the excellence of Madrasah Ibtidaiyah Muhammadiyah Dukuh lies in the extracurricular activity of Volleyball. This activity serves as a flagship program attracting the local community, with outstanding achievements such as securing the First Place in the Trenggalek Regency Volleyball Championship.